AB0904 Anti-Mullerian Hormone in A Cohort of Young Adult Women with Juvenile Idiopathic Arthritis. (10th June 2014) - Miceli, M.C.; Messuti, L.; Barini, A.; Canestri, S.; Gigante, M.R.; Barini, A.; Tolusso, B.; Gremese, E.; Ferraccioli, G.
Abstract : Background: Juvenile idiopathic arthritis (JIA) represents one of more common chronic disease of the childhood, affects young people before sixteen and persists into their reproductive years. These patients sometimes experience significant long-term morbidity while continuing immunosuppressive treatment. Anti-Mullerian hormone (AMH) is produced in the ovary by granulose cells of early developing follicles and in fertility clinics is used to estimate ovarian reserve which constitutes the number of primordial follicles. Objectives: To evaluate AMH serum levels in a cohort of young adult women affected from JIA with respect to healthy control comparable for age, to understand whether the disease may compromise ovarian reserve and to assess the influence of previous exposure to disease-modifying antirheumatic drug (DMARDs) and of other disease parameters on serum AMH concentration. Methods: 29 young women with a diagnosis of JIA, aged 18 to 26 years and having regular menses, and 20 healthy women comparable for age were recruited. AMH blood levels was assayed according to a 2-stage enzyme-linked immunosorbent assay (ELISA) technique using a commercially available kit (AMH Gen II ELISA; Beckman Coulter). Assessment of age, body mass index (BMI), disease duration, duration of previous treatments, 44 swollen and tender joint count, disease activity score on 44 joints (DAS), health assessment questionnaire (HAQ) were performed at the time of blood sample. Results: JIA patients had a mean age of 21.6±2.8 years, a disease duration of 12.0±6.1, a BMI of 24.2±5.1, a DAS of 1.25±0.65, and 6 (20.7%) were smokers. No significant differences were found between JIA and healthy subjects in AMH serum levels (6.1±2.3 vs 6.3±2.4 ng/ml, respectively, p=0.77). Considering the JIA cohort, 20 patients (69.0%) were treated with methotrexate (MTX) for a mean period of 4.2±3.6 years (range 1-13) and 15 (51.7%) with anti-TNF drugs for 4.9±1.9 years (range 1-8). 12 (41.3%) JIA women were treated with both MTX and anti-TNF. No correlations were found between AMH serum levels and patients age (p=0.93), disease duration (p=0.83) and duration of therapy with MTX (p=0.35) or anti-TNF (p=0.47). Dividing JIA patients according to MTX use, no differences were observed between MTX users and nonusers patients in AMH levels (6.0±2.0 vs 6.4±3.0 ng/ml, respectively, p=0.48), age, disease duration and other clinical characteristics. Similarly, AMH levels were comparable also between anti-TNF users and non users JIA subjects (p=0.11). Conclusions: In our JIA group of young adult JIA women, ovarian reserve seems not be changed by the presence of the disease, the long disease duration and the use of immunosuppressive drugs. These findings could be important for adult JIA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5009